Analisis Implementasi Model Pembelajaran Berbasis Daring pada Mata Pelajaran Biologi Kelas XI : (Implementation Analysis of Online-Based Learning Model in Class XI Biology) - A.Farid Rohmatulloh; Nur Khoiri; Ndzani Latifatur Rofi’ah (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Covid-19 had brought changes in various aspects of life, one of them in education, by implementing an online system. Implementing learning with an online system that changes suddenly makes the learning process from home ineffective because there are still many obstacles in the form of infrastructure and technical barriers faced by students, teachers, and parents. Teachers need to be more adaptive, creative, and innovative and choose relevant learning models to understand the material better. This research aims to describe the learning model used and analyze the implementation of the online-based learning model in biology class XI Senior SMA/MA negeri in Tuban Regency. The research approach used in this study is a qualitative approach with a descriptive method. Data collection methods are interviews, observations, and documentation, so that the research instruments used in this study are interview guidelines, observation sheets, and documentation. The analysis technique follows the data analysis of the Miles and Huberman model, which consists of data reduction, data presentation, and concluding. The results showed that SMAN 1 Grabagan, SMAN 1 Plumpang, and MAN 2 Tuban used the Contextual Teaching and Learning (CTL) learning model. While at MAN 1 Tuban using the Problem based learning (PBL) model, and SMAN 1 Soko using the online learning method. The implementation of the learning model at SMAN 1 Grabagan, SMAN 1 Plumpang and MAN 2 Tuban was carried out according to the syntax of the Contextual Teaching and Learning (CTL) learning model. However, several stages were not used. While the implementation of the learning model at MAN 2 Tuban was carried out according to the syntax of the Problem Based Learning (PBL) learning model and several stages were not implemented. The implementation of learning carried out at SMAN 1 Grabagan uses the online method. Abstrak. Covid-19 membawa perubahan bidang pendidikan dengan menerapkan sistem daring. Pembelajaran sistem daring yang berubah secara mendadak membuat proses belajar belum dapat dikatakan efektif secara keseluruhan, sehingga menjadi tantangan tersendiri bagi guru untuk lebih adaptif, kreatif, dan inovatif serta dapat memilih model pembelajaran yang relevan agar pemahaman siswa terhadap materi menjadi lebih baik. Penelitian bertujuan untuk mendeskripsikan model pembelajaran yang digunakan dan menganalisis implementasi model pembelajaran berbasis daring pada mata pelajaran biologi kelas XI SMA/MA negeri di Kabupaten Tuban. Penelitian menggunakan pendekatan kualitatif metode deskriptif. Metode pengumpulan data berupa wawancara, observasi, dan dokumentasi. Teknik analisis berupa reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan implementasi model pembelajaran di SMAN 1 Grabagan, SMAN 1 Plumpang, dan MAN 2 Tuban terlaksana sesuai sintaks Contextual Teaching and Learning meskipun beberapa tahapan tidak digunakan. Implementasi model pembelajaran di MAN 2 Tuban terlaksana sesuai sintaks Problem Based Learning meskipun beberapa tahapan tidak terlaksana. Implementasi pembelajaran di SMAN 1 Grabagan menggunakan daring method.